Comparisons of site-clearing and non-site-clearing Markovian queues with server failures and unreliable repairer. Issue 2 (4th March 2019) - Sun, Wei; Li, Shiyong; Liu, Wenyuan; Tian, Naishuo
Abstract: This paper compares the customers' balking behavior in site-clearing and non-site-clearing Markovian queues with server failures and unreliable repairer. That is, the system is subject to failures (catastrophes or normal failures) that occur when the server is at a functioning state, and it carries out the site-clearing mechanism if catastrophes occur while it carries out the non-site-clearing mechanism if normal failures occur. At a failure epoch, the server is turned off and all present customers are forced to leave the system in a site-clearing queue, whereas they start to experience a repair process in a non-site-clearing queue. After an exponential repair time, the server can be reactivated only with a probability p ( p < 1 ) . Once the server fails to be repaired, all present customers leave the system, and meanwhile the next repair time begins. Comparing the equilibrium and optimal balking strategies of customers for the two types of queues, we find that although customers more possibly face the bad outcome that can not be served eventually, they still prefer to select a site-clearing queue but not a non-site-clearing queue, which coincides with the social planner's preference. Moreover, the customers' equilibrium behavior more deviates from their socially optimal behavior in the site-clearing queues.